Growth and phosphorus accumulation in corn under doses of root phosphate and phosphite via leaf (Research, Society and Development, 2020)
The efficient use of phosphorus (P) in agriculture has been the main focus of research on this macronutrient. Phosphites, which have been considered plant stimulants, can contribute to increase the efficiency of the use of P by corn. The objective was to evaluate the influence of phosphite via leaf on the growth and accumulation of corn phosphorus in the initial growth phase under doses of P. An experiment was installed in a completely randomized design, in a 5 x 2 factorial scheme with four replications. At 45 days after planting, the plant height and stem diameter, shoot dry matter, stem and roots, contents, accumulation and P and the efficiency of using P (EUP) were evaluated. Phosphorus fertilization of corn, cultivated in chromium Luvisol in the initial stage is essential to increase its growth and the production of dry mass and accumulation of P. The phosphite applied via leaf did not produce additional benefit in growth, biomass production or phosphate nutrition of corn , but increased EUP at the intermediate dose (200 mg dm-3) of this nutrient.